Growing up Australian : exploring the ethnic identity negotiation of second generation Vietnamese youth in Perth (Curtin University, 2012)
This thesis is an exploration of the ethnic identity negotiation of a group of second generation Vietnamese young persons in Perth, and aims to uncover the content of ethnic identity; in other words, “what it means” and “what it looks like” to be Vietnamese or Australian. Adopting an interpretive narrative approach as research methodology, this research focuses on the familial and social experiences of this group of participants in uncovering dimensions of their ethnic identification and ethnic identity formation. Twenty second generation Vietnamese youth were invited to share their stories of growing up in Australia; this included ten male and ten female young persons. Using unstructured narrative interviews, this research explores the socio-cultural dimensions of their life experience as they navigate their transition into adulthood.Findings from this research suggest that the participants identify concomitantly as Vietnamese and Australian, giving strength to the notion that ethnic identity is but one of a multitude of social identities. The participants’ narratives also reveal that country of birth; cultural values and practices; ethnic socialization; and language spoken are dimensions salient to their ethnic identity formation process. In exploring their familial experiences, it was revealed that a disparity in values existed between the participants and their parents. This disparity often resulted in parent-child conflict during the participants’ adolescent years, in turn affecting their ethnic identity negotiation.Whilst it is acknowledged that the participants’ stories are not representative of all second generation Vietnamese youth in Perth, I argue that the Vietnamese in Perth are on an upward trajectory and have successfully integrated into the Australian mainstream culture. More importantly, their stories demonstrate that these young persons are skilful navigators as they negotiate between the two cultures. That is, rather than being caught “between” two cultures, these young persons are active members of both.